(untitled) (Eurasian Journal of Philology Science and Education, 2018)
This article investigates the importance of the term «concept» in mod ern human science. The essence of this notion is considered in the light of different scientific disciplines and approaches. On the basis of generaliza tion and analysis of theoretical works, devoted to the problem of concept, the properties and characteristics, the specificity of the artistic concept are revealed. In the process of analysis it was proved that in literary work, this term appears as a fixed option of individual author’s concept, which is accumulated in the semantic configuration of its concept sphere. The study of the artistic concept allows not only to penetrate in the nature of verbal creativity, generating artistic sense, but also to explore the art of communication. This paper examines the contribution of literature to the development of the concept sphere of people. It is stated that in modern philological science, this concept acts as a tool in studying the unity of the artistic world of the literary work and the writer’s national world